Analyse des aspects culturels et des valeurs culturelles dans le manuel Tendances A2 - Fauzi, Faris; Syaefudin, Mohamad (Universitas Negeri Semarang, 2025)
The data analysis used in this research is the content analysis technique. It is impossible to understand a particular culture without direct access to its language, as language is deeply embedded in culture. This research focuses on cultural studies with the theme of cultural aspects and cultural values of France in the book Tendances A2. It examines aspects of French culture according to the European community based on the CEFR concept and the cultural value of character according to Thomas Lickona. The research is qualitative, with a descriptive analysis approach. The techniques used to collect data in this study are of two kinds: documentation, listening, and note-taking. Daily life is the cultural technique that appears most often (17 aspects). The most common cultural value is respect (17 values).